PERLINDUNGAN HUKUM TERHADAP PEREMPUAN DALAM PROSES GUGAT CERAI (KHULU’) DI PENGADILAN AGAMA PALEMBANG - Syaifuddin Syaifuddin; Sri Turatmiyah (Faculty of Law, Universitas Jenderal Soedirman, 2012)
Divorce cases in the Islamic Court of Palembang (Pengadilan Agama Palembang) becomes the top of the list, during the year 2009 (72%), 2010 (72%) and 2011 (in June) about 70%. The purpose of this study is to analyze the causes of high divorce rate happening in the city of Palembang, beside to explain the forms of legal protection and analyzes the factors that becoming obstacles for the wife in a filed divorced. The research was conducted with a Normative-Juridical approach which is completed with Empirical Juridical, The location is in the jurisdiction of the Islamic Courts in Palembang (Pengadilan Agama Palembang. Causes of high divorce cases in the city of Palembang, among others: a) economic factors; b) Lack of responsibility; c) a young age and no permanent employment; d) cheating and Unhealthy polygamy as well as domestic violence. Legal protection towards wives who filed the divorce, in Indonesian legal system has been arranged as equality in law and equal treatment before the law and the right to justice. Barriers toward the wife filing the divorce among others: cultural factors, economic dependence, lack of knowledge, and bias Perspective of judges who tend to blame the women, the long process of trial and expensive fees to be paid, also Over valued self-esteem in Indonesian people's community, as well as women's rights arenot easily executed. Key words: legal protection, divorce process